New insights explain that organic agriculture as sustainable agriculture enhances the sustainable development of medicinal plants - Jiang, Linlin; Chen, Yuan; Wang, Xiaoqin; Guo, Wenfang; Bi, Yaqiong; Zhang, Chunhong; Wang, Jianhua; Li, Minhui (Frontiers in Plant Science, 2022)
As global health care demand continues to increase, medicinal plant productivity must progress without exhausting critical environmental resources. Hence, it is important to explore practices that can improve the quality, safety, and sustainability of medicinal plants, as well as ecological stability. Organic farming has recently gained significance as a sustainable cultivation alternative owing to increased awareness of the adverse effects of conventional cultivation method. Here, this study aimed to investigate the feasibility of organic farming as a solution for sustainable cultivation of medicinal plants from multiple perspectives and long-term benefits to the environment. Organic agricultural practices of medicinal plants were evaluated from a multi-dimensional perspective (environment, economy, and society) using extensive research data and literature and field surveys. Data from medicinal plant cultivation in Inner Mongolia were acquired for 76 sites from 4 data stations between 2014 and 2021. Data analysis revealed that organic medicinal plants can improve safety by reducing pesticide exposure risks. Simultaneously, organic agriculture of medicinal plants can improve biodiversity by effectively reducing pesticide and fertilizer use, which also provides natural safe products for health care. With the improvement of quality, the retail price will have a certain advantage, which will improve the income of farmers. Moreover, organic agriculture enhanced profitability because of the higher organic premium on medicinal plant products and improved ecosystem stability by increasing plant diversity. The findings of this study suggest that organic cultivation strategies can improve the quality and safety of medicinal plants and further provide a basis for promoting the sustainable development and ecological stability of medicinal plants. However, not all medicinal plant cultivators are guaranteed to adopt organic farming practices, but if all technological elements are correctly applied, the system can be maintained sustainably to expand the area of organically cultivated plants in the future.